LAYANAN BIMBINGAN PRIBADI SOSIAL DALAM MENUMBUHKAN PRILAKU POSITIF SISWA - Rima Faiqotul Affa; Nurus Sa’adah (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2021)
The era of globalization is a door for students to explore and open up insight into society, with various impacts that occur in the current era, but it does not rule out that it will be one of the significant changes to the younger generation. The behavior produced by this era of globalization is due to a lack of supervision and many other influences. This study aims to describe personal social guidance services in fostering positive student behavior. The method used in this study is a qualitative method with a literature review. The researcher collected several journals related to the focus of the discussion after analyzing it. Based on the results of the literature there are several factors, namely the personal experience of others and culture, with personal social guidance services to foster positive behavior for students more effectively using modeling techniques. Most students will imitate the things around them, motivation without a real example will not move the heart to explore itself so that it can find solutions to every social problem. Most of the students who are studying SMA / SMK